In vitro cultured primary roots derived from stem segments of Cassava (Manihot esculenta) can behave like storage organs - Medina, Ricardo Daniel (2007)
Fil: Medina, Ricardo Daniel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.